2008
DOI: 10.1175/2007jpo3890.1
|View full text |Cite
|
Sign up to set email alerts
|

Observations of the Dispersion Characteristics and Meridional Sea Level Structure of Equatorial Waves in the Pacific Ocean

Abstract: Spectral techniques applied to altimetry data are used to examine the dispersion relation and meridional sea level structure of wavelike variability with periods of about 20 to 200 days in the equatorial Pacific Ocean. Zonal wavenumber-frequency power spectra of sea surface height, when averaged over about 7°S-7°N, exhibit spectral peaks near the theoretical dispersion curves of first baroclinic-mode equatorial Kelvin and Rossby waves. There are distinct, statistically significant ridges of power near the firs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
42
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(50 citation statements)
references
References 58 publications
8
42
0
Order By: Relevance
“…2a). The 33-day TIWs also have a signal south of the equator, near 58S, but its amplitude is several times smaller, as expected from previous work (e.g., Chelton et al 2000;Lyman et al 2005;Farrar 2008). …”
Section: Introductionsupporting
confidence: 85%
See 3 more Smart Citations
“…2a). The 33-day TIWs also have a signal south of the equator, near 58S, but its amplitude is several times smaller, as expected from previous work (e.g., Chelton et al 2000;Lyman et al 2005;Farrar 2008). …”
Section: Introductionsupporting
confidence: 85%
“…1; see also Farrar 2008;Shinoda et al 2009). This spectral peak is associated with TIWs, but a complete description cannot come from sea level fluctuations alone.…”
Section: Introductionmentioning
confidence: 90%
See 2 more Smart Citations
“…It is demonstrated that wavenumber-frequency spectral analysis is useful for identifying signals of atmospheric equatorial waves including Yanai waves, and for isolating their structure. While the observed dispersion relationships of equatorial Kelvin and Rossby waves in the ocean were identified recently by wavenumber-frequency spectra of satellite-derived sea surface height (SSH) (Wakata 2007;Farrar 2008;Shinoda et al 2009), the resolution of the satellite altimeter data was insufficient to describe oceanic Yanai waves in frequency-wavenumber space until recently. This situation has begun to change because of multiple satellite launches in recent years.…”
Section: Introductionmentioning
confidence: 99%